Analisis Teknik Observasi Dalam Pembelajaran Pendidikan Anak Usia Dini - Suwaryaningrat, Ni Dewi Eka (Peneliti.net, 2023)
Observation in early childhood education is an activity carried out by teachers in observing students in order to obtain information about various aspects of development and progress in the learning carried out. Observations carried out continuously are the same as teachers who are developing